The Relationship between Family-Owned Business and the Success of Small Medium Enterprise - Rian Adriansah; Teten Mohammad Sapril Mubarok (Research Collaboration Community (RCC), 2023)
Most of large and successful companies are derived from family businesses that grow successfully. This business success will only happen if the family-owned business is able to create appropriate company structure and apply good management principles so that the company will develop and survive from one generation to another. A common problem found in family businesses is internal conflict in which the family member has his own interest that could interrupt the business. The differences in opinion and self-interested factors are common things in family business. Another problem that a family business should deal with is external factors. Competitive companies, politics, government regulation are some issues which are difficult to face. Those problems could give impact to the family-owned business. This study was aimed at finding out the problem solutions of family business by analyzing the relationship between family-owned business and its success in SMEs. The research method used was quantitative by using causal design. The primary data was taken from 30 respondents who are the owners of family businesses in SMEs. The technique of data analysis used was simple linear regression in SPSS software version 26. The result of this study confirmed that there was a relationship between family-owned business and its success in SMEs. The roles of family members and good management are the success keys in family businesses and SMEs. This study is beneficial to develop family small business in forms of applied theory that the business ownership has relationship and is able to give impacts towards the business successes.